Risk Factors of Cardiovascular Disease (CVD) - A Critical Scientific Review - Saurabha Nayak,; Bipin Bihari Khuntia,; Asif Hasan, (International Journal of Ayurveda and Pharma Research, 2022)
Cardiovascular Diseases (CVDs) are taking the biggest toll on human health since the last few decades. Around the middle of the 20th century, morbidity and mortality due to CVDs began to increase exponentially due to drastic change in lifestyle and rapid urbanization. At that point of time a very little was known about its causes or risk factors. Identification of risk factors is crucial in planning the treatment and prevention strategies for any disease. Profound research works have been conducted worldwide to identify risk factors of CVDs. Conventional risk factors like obesity, smoking, hypertension, diabetes, dyslipidemia, physical inactivity etc are already given due importance in risk prediction, prevention and management of CVDs. The risk assessment tools available at present are mainly based on these conventional risk factors. Even after adjusting the conventional risk factors, CVD related morbidity and mortality are still growing. Moreover CVDs are now reported at an early age. Hence there is also a need to identify novel risk factors which can be helpful in predicting and identifying CVDs earlier. The future of CVD risk assessment is an integration of both traditional as well as emerging risk factors for better prediction, diagnosis and planning therapeutic and preventive interventions of CVDs.